Factors Influencing Dropout Rate in Bachelor’s Degree at Nilkantha Multiple Campus - Subedi, Yuba Raj (The EFFORTS, Journal of Education and Research, 2022)
This paper primarily aimed to investigate the factors influencing dropout rate in bachelor's degree and explore the reasons behind students' dropout. A survey research design had been taken to describe the dropout rate and 30 dropout students of bachelor's degree were selected as the respondents through judgmental sampling under non-random sampling procedure. Telephone interviewing was used as the tool for collecting the required information. This study based on the theoretical tenets of Maslow's Hierarchy of Needs, Motivation and Engagement, and Cognitive Load Theory. This study found that student-related indicators, campus-related indicators and family-related indicators play significant role in determining dropout rate. The main reasons of dropout explored from student-related indicators were their low academic achievement in examination and irregularity in class; campus-related indicators were lack of academic support, feedback, motivation and encouragement from teachers, and problem of institutional information system; and lastly, family-related indicators were lack of financial support from home and, different family problems. The implication of this study is to solve the problem of dropout in the development of higher education programs in Nepal.